Prevalence of Absence of Palmaris Longus Muscle in Kashmiri Population - Muhammad Junaid khan, Muhammad Saeed Shafi, AbaidullahShoukat, Khawaja Abrar Ahmed, Saman Azad, Muhammad Zaheer-ud-Din Ayub,Zohaib Ilyas, Kinza Imtiaz, Amina Kanwal, Rabia Tabbsum, Nimrah Masood, Saeeda Rashid, Fahima Shoukat,Amber Latif, (Journal of Rawalpindi Medical College, 2016)
Background: To determine prevalence of absence of Palmaris Longis (PML) in Azad Jammu and Kashmir population. Methods: A descriptive, cross-sectional study carried out in seven districts of AJ&K. A pilot test questionnaire was used to collect demographic data by voluntary participants after an informed written consent. Master trainees were trained at AJK Medical College, Muzaffarabad, who were involved in data collection and clinical testing for the absence of PML and its effects on0 their daily activities. Results: Out of 700 subjects,132(18.9%) had agenesis of PML; 245 (35%) were left hand dominance and 455(65%) right hand dominance. among left handed 49 (33.9%) subjects had agenesis of PML. Among 455 total right hand dominance 83 (18.2%) subjects had agenesis of PML. Overall 28 subjects had unilateral and 104 bilateral agenesis of PML.This absence of PML did not affect their routine activities. Morphologically, different tendons of PML were also found. Conclusion:Prevalence of absence of PML in Kashmir was found in 18.9%. Its agenesis varies with body side, sex, and hand dominancy. Right hand and bilateral agenesis was greater than left hand dominance and unilateral respectively. Significance difference was observed between male and female agenesis(P< 0.05).